Christ’s Love Moves the Church: An Ecumenism of the Heart - Durber, Susan (The ecumenical review, 2021)
The ecumenical movement stands in need of renewal, a renewal inspired and moved by a depth and warmth of love. It has, for too long, been dominated by discourses of the mind (and particularly by styles of thinking of the West and the global North). A renewal that draws on the knowledge of body, mind, and heart might resonate with a much broader global constituency and fire passion and commitment in people who now pull back from what they experience as abstract forms shaped by colonial power and culture. A unity founded in a loving communion may open up new possibilities, and a new language of the heart might stir a revival in the ecumenical movement.